Restrukturisasi Organisasi Perangkat Daerah Kecamatan di Kabupaten Kolaka Utara - Taufik Hidayat (Publik : (Jurnal Ilmu Administrasi), 2018)
This study aims to analyze the process of organizational restructuring of regional devices in the scope of North Kolaka District Government (Case Study of Tiwu and Lasusua Sub-districts) and analysis of typology and size of the organization of the Kecamatan. This research was conducted in North Kolaka Regency using mix method approach. The research shows that the process of restructuring of regional apparatus organization in North Kolaka district especially in Tiwu District and Lasusua sub-district institutional redesign has not been through the stages and process of effective and efficient institutional arrangement, the formation process of the formulation team, the political process of policy determination, the process of determining type and magnitude of sub-district organization, organizational structure and working procedures, duties and sub-district functions that overlap one affair with other affairs, and the lack of socialization of institutional arrangement policy so that the process of organizational restructuring of sub-district has not been rational, effective and efficient as well as determination of tipelogi and the size of Tiwu and Lasusua sub-district organizations have not been based on analysis of the main workload of government affairs in general variables and technical variables in a rational, effective and efficient manner. Penelitian ini bertujuan menganalisis proses restrukturisasi organisasi perangkat daerah di lingkup Pemerintah Kabupaten Kolaka Utara (Studi Kasus Kecamatan Tiwu dan Kecamatan Lasusua) dan analisis tipelogi dan besaran organisasi Kecamatan tersebut. Penelitian ini dilaksanakan di Kabupaten Kolaka Utara dengan menggunakan pendekatan mix method. Penelitian menunjukkan proses restrukturisasi organisasi perangkat daerah di Kabupaten Kolaka Utara khususnya dalam redesain kelembagaan Kecamatan Tiwu dan Kecamatan Lasusua, belum melalui tahapan-tahapan dan proses penataan kelembagaan yang efektif dan efisien, proses pembentukan tim perumus (kepanitiaan), proses politik penetapan kebijakan, proses penentuan tipe dan besaran organisasi Kecamatan, Struktur Organisasi dan Tata Kerja, Tugas Pokok dan Fungsi Kecamatan yang tumpang tindih antara satu urusan dengan urusan yang lain, serta kurangnya sosialisasi kebijakan penataan kelembagaan sehingga belum terwujudnya proses restrukturisasi organisasi Kecamatan yang rasional, efektif dan efisien serta penentuan tipelogi dan besaran organisasi Kecamatan Tiwu dan Kecamatan Lasusua belum berdasarkan analisis beban kerja utama urusan pemerintahan dalam variabel umum dan variabel teknis secara rasional, efektif dan efisien.